Occurrence of nodular gill disease in farmed brown trout (Salmo trutta L.) - Perolo A; Accini A.; Lunelli F.; Dalla Pozza M.; Gustinelli A.; Menconi V.; Fioravanti M. L.; Quaglio F. (2017)
Introduction Nodular gill disease (NGD) represents one of the most serious pathology affecting freshwater farmed rainbow trout (Oncorhynchus mykiss) in Italy. This disease has also been observed in arctic char (Salvelinus alpinus) and Chinook salmon (Oncorhynchus tshawytscha) cultured in freshwater environment. The first case of branchitis associated with amoebic infection is detected in farmed brown trout (Salmo trutta L.) in March 2017, during an investigation of NGD in rainbow trout in the province of Trento (Northern Italy). Methodology In a NGD affected rainbow trout farming an outbreak of low mortality occurred in brown trout in one earth tank supplied by spring water with temperature of 6°C. The average weight of the fish was 20-25g. Twenty five fish from the affected tank were collected for necropsy, microscopical and parasitological analysis. Gills were dissected and fixed in 10% neutral buffered formalin solution for histological examination. The samples were dehydrated, embedded in paraffin wax, sectioned (4 µm) and stained with Hematoxylin Eosin and Giemsa solution. Results The fish did not exhibit the typical respiratory symptoms described in NGD of the rainbow trout. The gill tissue appeared pale and swollen at the necropsy with whitish nodules in 9 out of 25 sampled trout. Microscopically numerous Gyrodactylus spp. were observed on the skin. The affected gills showed a proliferative reaction of some filaments, especially in the distal part. These lesions were typical of NGD infection. The microscopic examination of gill tissue revealed the presence of amoebic organisms (approximately 15 x 20 µm). The histology showed multi-focal epithelial hyperplasia of the gills causing lamellar fusion, mucous cells hypertrophy, cellular necrosis and presence of limited number of amoebae along the surface of the affected filaments in 6 out of 25 collected gills. Discussion Despite absence of respiratory symptoms and high mortality rate, gill proliferative lesions associated with amoebae shows that brown trout ...